Profil Hematologi dan Protein Plasma Darah Sapi Perah Laktasi di Kelompok Ternak Bojong Kawung Pasir Jambu dengan Pemberian Feed Supplement - Januardani, Astri Abilail; Tanuwiria, Ujang Hidayat; Mushawwir, Andi (Universitas Islam Negeri Alauddin Makassar, 2023)
Twenty lactating dairy cows with the 1st, 2nd, and 3rd lactation periods and 1st to 5th lactation months as research objects to determine the effect of giving feed supplements on hematology and blood biochemistry. The experimental design used was a completely randomized design (CRD) with an experimental method consisting of 4 treatments and 3 replications. Each treatment consisted of 5 lactating dairy cows. The study was conducted for 10 weeks with the first 2 weeks being used as the adaptation stage. The treatments given were P0 = basal ration without feed supplement (control), P1 = 60% forage + 40% concentrate (97% concentrate + 3% protein by-pass), P2 = 60% forage + 40% concentrate (95% concentrate + 3% protein by-pass + 2% Ca-PUFA), and P3 = 60% forage + 40% concentrate (93% concentrate + 3% protein by-pass + 2% Ca-PUFA + 2% organic minerals). Blood sampling was carried out for each cow so that 20 blood samples were obtained. Blood sampling was carried out twice. The parameters observed in this study were the hematological profile which included Red Blood Cell (RBC), hemoglobin, hematocrit, Man Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin Concentration (MCHC), and platelets. Blood biochemical parameters include glucose, total protein, albumin, and globulin. The results showed that feeding supplementation had a significant (P<0.05) effect on hematology and blood biochemistry, except MCV, MCHC, glucose, and albumin. The hematological and blood biochemical profiles of lactating dairy cows remain optimal through feed supplements in the form of protein by-pass, Ca-PUFA, and organic minerals.